Cell-in-cell structure in cancer: evading strategies from anti-cancer therapies - Okuyama, Kohei; Fukushima, Hiromasa; Naruse, Tomofumi; Yanamoto, Souichi (Frontiers in Oncology, 2023)
One of the regulated forms of cell death is the cell-in-cell (CIC) structure, in which a surviving cell is engulfed by another cell, a mechanism that causes the death of the engulfed cell by an adjacent cell. Several investigators have previously shown that the presence of CICs is an independent risk factor significantly associated with decreased survival in patients with various types of cancer. In this review, we summarize the role of CIC in the tumor microenvironment (TME), including changes and crosstalk of molecules and proteins in the surrounding CIC, and the role of these factors in contributing to therapeutic resistance acquisition. Moreover, CIC structure formation is influenced by the modulation of TME, which may lead to changes in cellular properties. Future use of CIC as a clinical diagnostic tool will require a better understanding of the effects of chemotherapy on CIC, biomarkers for each CIC formation process, and the development of automated CIC detection methods in tissue sections of tumor specimens.